The elements of accounting : an introduction - Whittington, Geoffrey (Cambridge University Press, 1992)
This book is a clear and concise introduction to the content and structure of accounting statements and the double entry system which underlies them. It is intended as a first introduction to the subject and assumes no previous knowledge or experience of accounting. Worked numerical examples are an integral part of the exposition, and exercises (with solutions) are provided. There are also chapters on the interpretation of accounts, on accounting for price changes, and on broader aspects of accounting. The emphasis throughout is on understanding fundamental principles rather than on detailed practical procedures. The book is primarily addressed to university students who are meeting the subject for the first time, and is a first introduction for students preparing for professional examinations, giving them a grounding in the fundamental nature of accounting which is lost in other more compendious introductory texts.